2023
DOI: 10.1161/circimaging.122.014963
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Mechanics Relate to Myocardial Fibrosis and Ventricular Arrhythmias in Patients With Mitral Valve Prolapse

Abstract: Background: The relation between ventricular arrhythmia and fibrosis in mitral valve prolapse (MVP) is reported, but underlying valve-induced mechanisms remain unknown. We evaluated the association between abnormal MVP-related mechanics and myocardial fibrosis, and their association with arrhythmia. Methods: We studied 113 patients with MVP with both echocardiogram and gadolinium cardiac magnetic resonance imaging for myocardial fibrosis. Two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…23 Molecular histopathology further differentiates diffuse myxomatous disease from more localized disruption in fibroelastic deficiency, while imaging valve strain can innovatively link basic and mechanical changes. 24 In future, interactions of valves with annular and ventricular structures provide opportunities to study the intersection of biomechanics and molecular changes through understanding how flattening the mitral annular saddle can augment leaflet stresses and worsen mitral valve prolapse 25 ; how prolapse-induced forces can generate localized, proarrhythmic ventricular fibrosis 26 ; and how local and global remodeling of the ischemic or myopathic ventricle can trigger intrinsic valve changes.…”
Section: Gaps In Knowledge: Mitral Valve Diseasementioning
confidence: 99%
“…23 Molecular histopathology further differentiates diffuse myxomatous disease from more localized disruption in fibroelastic deficiency, while imaging valve strain can innovatively link basic and mechanical changes. 24 In future, interactions of valves with annular and ventricular structures provide opportunities to study the intersection of biomechanics and molecular changes through understanding how flattening the mitral annular saddle can augment leaflet stresses and worsen mitral valve prolapse 25 ; how prolapse-induced forces can generate localized, proarrhythmic ventricular fibrosis 26 ; and how local and global remodeling of the ischemic or myopathic ventricle can trigger intrinsic valve changes.…”
Section: Gaps In Knowledge: Mitral Valve Diseasementioning
confidence: 99%
“…Direct evidence of increased forces on the papillary muscle due to single or bileaflet MVP was demonstrated recently using the elaborate ex vivo simulator at the Woo laboratory at Stanford and a novel system to adjust the primary chordae tendineae length without manipulating any other elements of the MV and subvalvular structures (see Figure 13) [44]. Furthermore, utilizing advanced mechanical analysis based on an echocardiography-derived LV strain, it was found that altered longitudinal strain is seen in the basal inferolateral myocardium, situated between the mitral annulus and papillary muscles in patients with MVP compared with healthy controls [155]. In addition, studies have observed a decrease in papillary muscle systolic shortening associated with MVP, which may reflect increases in the tissue stiffness due to either PM fibrosis or opposing stretching forces as a results of the increase in tension from the prolapsing valve [156].…”
Section: The Valve Pulls On the Ventriclementioning
confidence: 99%
“…Computationally, Zhang and colleagues [2019] also demonstrated that this device induces abnormal strains in the ventricular wall. Taking into account the current evidence for abnormal mechanics in MVP due to increased traction forces that are independently associated with the presence of localized fibrosis and the occurrence of life-threatening ventricular arrhythmias [155], this may have larger implications for long-term outcomes; however, it remains a topic of much needed ongoing research efforts.…”
Section: Surgical Repair Techniquesmentioning
confidence: 99%
“…Since adult cardiac tissue lacks endogenous stem cells with in vivo regenerative potential, the loss of terminally differentiated contractile cells cannot be replenished [ 10, 11,12 ] . Moreover, during the late stage of fibrosis, myofibroblasts undergo apoptosis, the ECM stiffens, and the abundant matrix infiltrates between the remaining functional cardiomyocytes (CMs), thus leading to arrhythmic events which compromise the heart function [ 7,13 ] . Different strategies have been devised to modulate cardiac fibroblasts activation and reduce the symptoms of cardiac fibrosis with contrasting results.…”
Section: Introductionmentioning
confidence: 99%